The appearance of everyday life events in photographs from the Qajar era - A. Heydari; S. Erfani (Taḥqīqāt-i Farhangī-i Īrān)
The present study aims to investigate everyday life events captured in the first photographs of Iranian history. As such, by focusing on a collection of photo albums from Naseri and Mozaffari eras (two Qajar rulers) and by scrutinizing them, an attempt was made to elucidate the representation patterns and modes, through which, everyday life appeared in those photos. With an emphasis on semiology and taking into account the time-space, transcendental and immanent concepts, the paper tries to examine visible and invisible patterns of everyday life in those photographs. For that sake, the images were classified into six categories: Transcendental places, photography of nature, non-royal settings, iconography out of place and time, exotic eroticism, and everyday life. The study explores the relationship between each category and the presence of everyday life, focusing on archetype photos to provide in-depth analysis and discussion.